Characterization of Bacillus subtilis strains as candidates for the preparation of animal additives - Milián, Grethel; Rondón, Ana; Pérez, M.; Bocourt, R.; Rodríguez, Marlén; Arteaga, Fátima; Portilla, Yadileiny; Pérez, Y.; Beruvides, A.; Laurencio, Marta (Cuban Journal of Agricultural Science, 2017)
The strains C-31, C-34 and E-44 of Bacillus subtilis, sub species subtilis were characterized for their use in the elaboration of animal additives destined for animal production. The studied strains belong to the strains collection from the Centro de Estudios Biotecnológicos de la Facultad de Ciencias Agropecuarias de la Universidad de Matanzas and to the Instituto de Ciencia Animal. For the characterization of these strains, growth capacity, endospores production, enzyme production, antimicrobial activity and response to 25 broad spectrum antibiotics were considered. The results showed that the three strains have high growth capacity and endospore production, were able to inhibit Gram positive and Gram negative microorganisms; in addition to showing sensitivity to the 25 antibiotics evaluated. This allows inferring that these strains show favorable ranges to be used as animal additives, which are currently a promising alternative to the use of antibiotics as growth promoters. Key words: antimicrobials, sensitivity, antibiotics, enzymes, Bacillus subtilis